ONLINE PERSONA OF VTUBER AYUNDA RISU CH: SOCIOLINGUISTIC STUDY - Fahri Aolia; Nugraheni Widianingtyas (PRIMACY Journal of English Education and Literacy, 2024)
With the pandemic COVID-19 outbreak throughout the world, the number of social media users multiplied by a massive number. YouTube streaming platforms becomes a place where people spend most of their time online. The trend called Virtual YouTubers becomes popular during the pandemic. One of the prominent factors of VTuber was their persona. VTubers Ayunda Risu becomes the subject of this research to give insight into how VTuber can manifest their persona to attract or retain their audience. By following the guidance of the qualitative method, this article focused on analyzing the live streams done by Ayunda Risu. Combining the method of qualitative study simultaneously with the author's experience in VTuber entertainment, this article creates a conclusion corresponding to how VTubers manifest their persona to attract and retain their audience. The study concludes that persona manifests as a result of the audiences preference. However, VTubers' inner personality also becomes the essential element to manifest their persona and online build personal branding, which as a result can gain or retain an audience.